Henri de Lacaze‐Duthiers and the ascidian hypothesis - Jessus, Catherine; Laudet, Vincent (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2024)
In 1830, Cuvier and Geoffroy Saint‐Hilaire confronted each other in a famous debate on the unity of the animal kingdom, which permeated the zoology of the 19th century. From that time, a growing number of naturalists attempted to understand the large‐scale relationships among animals. And among all the questions, that of the origin of vertebrates was one of the most controversial. Analytical methods based on comparative anatomy, embryology and paleontology were developed to identify convincing homologies that would reveal a logical sequence of events for the evolution of an invertebrate into the first vertebrate. Within this context, several theories have clashed on the question of the identity of the ancestor of vertebrates. Among the proposals, a group of rather discrete organisms, the ascidians, played a central role. Because he had discovered an ascidian with a particularly atypical larval development, the Molgula, Henri de Lacaze‐Duthiers, a rigorous and meticulous naturalist, became involved in the ascidian hypothesis. While the visionary mind of Lacaze‐Duthiers led him to establish a particularly innovative methodology and the first marine biology station in Europe, at Roscoff, the tailless tadpole of the Molgula prevented him from recognizing the ancestor of vertebrates. This old 19th century story echoes the ever‐present questions driving the field of Eco‐Evo‐Devo. In the 19th century, Henri de Lacaze‐Duthiers, a rigorous and meticulous malacologist became involved in the debate on the origin of vertebrates and their relationships with ascidians. His discovery, meticulous description and experimental analysis of Molgula and its tailless tadpole prevented him from recognizing the relationships between ascidians and vertebrates. The reason behind this failure highlights the biases and constraints of comparative zoology at the time and echoes the ever‐present questions driving the field of Eco‐Evo‐Devo. Research Highlights In the 19th century, ascidians were important in the debate over vertebrates’ origins. Henri de Lacaze‐Duthiers discovered Molgula and its tailless tadpole and this prevented him from recognizing the relationships between ascidians and vertebrates. This old story echoes the ever‐present questions driving Eco‐Evo‐Devo.